Motivational factors among social work undergraduates in online education during the post-COVID-19 era - Athirah, Azhar (SAGE Publications Inc., 2022)
This essay summarises social work students’ experiences with online learning during a pandemic and investigates motivational factors post-pandemic. Post-COVID, 56 percent prefer hybrid learning. Students reported that they were the primary source of motivation for online classes, followed by course instructors and the environment.